Analysis of Maqasid al-Syari'ah (Primary Maslahat) on the Practice of Mute Marriage Contracts in Songing Village, South Sinjai District, Sinjai Regency - Muh. Risal; BN, Andi Muh. Taqiyuddin; Muammar Muh. Bakry; Samsidar Jamaluddin; Suprijati Sarib (Jurnal Marital: Kajian Hukum Keluarga Islam, 2025)
This study aims to examine the Analysis of Maqasid al-Syari'ah (Primary Maslahat) on the Practice of Mute Marriage Contracts in Songing Village, South Sinjai District, Sinjai Regency. This is a qualitative study. The research design is field research. Data collection methods in this study include observation, interviews, and documentation. The results of this study indicate that the practice of mute marriage contracts in Songing Village, South Sinjai District, Sinjai Regency, is inconsistent with the Marriage Law of 1974, Article 2, Paragraphs 1 and 2, as well as KHI Article 4, which is considered inconsistent with one of the primary objectives of Maqasid al-Syari'ah, namely maslahat primer, hifz al-Din. This is due to the contradiction between the marriage contract practices and Islamic law, specifically the consensus of Islamic scholars, which is the primary cause of the violation of the Marriage Law of 1974, Article 2, Paragraph 1, and KHI Article 4. Furthermore, hifz al-Nasl. This is because the marriage is not recognised due to its violation of the Marriage Law of 1974, Article 2, Paragraph 1, and therefore the marriage is not registered as mentioned in the subsequent paragraph. This has implications for the status of children in the marriage under the applicable law in Indonesia. The subsequent effect is chaos in the realm of hifz al-Mal/maintenance/guardianship of property. This reality causes serious issues regarding the inheritance status of children and spouses, as well as joint property. Regarding the legal status of the marriage under Sharia law. This is exempted if the marriage officiant was unaware of the consensus of the scholars.